The Dynamics of Change in George Bernard Shaw’s Drama: A Study of Saint Joan, Pygmalion, and Arms and the Man - Zayed Hussein Saleh Al-Mudhafar; Intan Maulina (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
This study aims to examine how George Bernard Shaw dramatizes the idea of change as both a moral and intellectual necessity for human and social progress. It seeks to analyze how Shaw's conception of transformation functions as an ethical, social, and artistic principle across three of his major plays: (Saint Joan, 1923), (Pygmalion, 1913), and (Arms and the Man, 1894). This study explores George Bernard Shaw’s dramatic representation of change as a dynamic social, moral, and intellectual process across these influential plays. Shaw’s theatre functions as a critique of stagnation, whether political, religious, or personal and as a call for continuous re-evaluation of inherited ideas. By dramatizing moments of transition within individuals and societies, Shaw transforms the stage into a forum for intellectual evolution. This paper argues that Shaw conceives of change not as an abstract ideal but as a moral imperative, one that disrupts complacency, exposes hypocrisy, and fosters authentic progress. Using a combination of textual analysis, New Historicist and socio-critical frameworks, the research demonstrates that Shaw’s characters Joan of Arc, Eliza Doolittle, and Captain Bluntschli embody catalysts of transformation who question dogma and reveal the tension between reality and illusion. Through their struggles, Shaw redefines heroism as intellectual courage and moral adaptability rather than mere physical valour or social conformity. The study concludes that Shaw’s theatre remains profoundly relevant to modern audiences for its vision of change as both a disruptive and regenerative force, essential for the renewal of human consciousness and social order.